Advertisement Remove all ads

InΔABC with Usual Notations, Prove that 2a {Sin^2(C/2)+Csin^2 (A/2)} = (a + c - b) - Mathematics and Statistics

 

In ΔABC with usual notations, prove that 2a `{sin^2(C/2)+csin^2 (A/2)}` = (a +   c - b)

 
Advertisement Remove all ads

Solution

`sin^2theta =(1-cos2theta)/2`

`L.H.S=2{asin^2(C/2)+csin^2(A/2)}`

`=2{(a(1-cosC))/2+(c(1-cosA))/2}`

=a-acosC+c-ccosA

=(a+c)-(acosC+ccosA)

=a+c-b

R.H.S

2a `{sin^2(C/2)+csin^2 (A/2)}` = (a +   c - b)

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×